Exploring Hospital Brand Image: A Mixed-Method Study on Social Security Patients - Daniel Ginting; Nina Fentiana (Jurnal teknologi Kesehatan Borneo, 2024)
Limited literature on patient perceptions of hospital services occurs in Indonesia. The study aims to explore the perceptions of social security agency patients towards the hospital's brand image in the outpatient and inpatient service environment at Laras Hospital, Simalungun Regency, North Sumatra Province. The research method used a mixed method (quantitative and qualitative) on 100 patients in October-December 2024. Sampling was carried out purposefully, and data analysis was carried out univariately and thematically. The image of the hospital in outpatient services was very good (91.9%) and good (79.6%) in inpatient services. The themes that emerged from the patient's perspective on brand image were the quality of doctor services, the value of services perceived by patients, facilities, and equipment in services. The results of the study emphasise the importance of health service providers improving the quality of doctors and nurses perceived according to patient needs. Strengthening this area will improve patient perceptions of the hospital's brand image.